Angel of Greenwood - Pink, Randi (Feiwel and Friends, 2021)
Randi Pink's The Angel of Greenwood is a historical YA novel that takes place during the Greenwood Massacre of 1921, in an area of Tulsa, OK, known as the "Black Wall Street."